Diagnosis dan penatalaksanaan tuberkulosis sistem saraf pusat - Prima Yogi; I Putu Andrika; I Gede Ketut Sajinadiyasa; I Made Bagiada (DiscoverSys Inc., 2021)
Introduction: Central nervous system (CNS) tuberculous are the most dangerous form of extrapulmonary TB. CNS tuberculous can present as meningoencephalitis, intracranial tuberculomas, and vasculitis. CNS tuberculous accounts for about 1% of all TB cases and is associated with high mortality. Tuberculous meningoencephalitis commonly presents with classic symptoms of fever, headache, meningism (neck stiffness), seizures as well as focal neurologic deficits, and altered consciousness. The diagnosis and treatment of CNS tuberculosis is still a formidable clinical challenge.Case report: Patient presented with fever, headache, meningismus, convulsion, and decreased consciousness. CT scan showed cerebral tuberculoma in the left parietal lobe. Examination gene-Xpert of the cerebrospinal fluid showed Mycobacterium tuberculosis. The patient was given category 1 of anti-tuberculosis drugs.Conclusion: CNS tuberculosis has non-specific symptoms, difficult diagnosis, and high mortality. In this case report, the diagnosis of CNS tuberculosis was established based on the presence of Mycobacterium tuberculosis on the CSF molecular rapid test examination, and a CT scan of the head with contrast found cerebral tuberculoma.